Adjuvant chemoradiotherapy in resected gallbladder cancer: A SEER-based study. Issue 3 (March 2023) - Jiang, Yong; Jiang, Liyong; Li, Hongxin; Yuan, Shuai; Huang, Songhan; Fu, Yingda; Li, Shenhao; Li, Feiyu; Li, Qingbin; Yan, Xiangyu; Chen, Ji; liu, Jun
Abstract: Background: The prognosis of gallbladder cancer (GBC) is dismal. This study aimed to compare the outcomes of adjuvant chemoradiotherapy (ACR) with those of surgery alone (S) and adjuvant chemotherapy (AC). Method: The Surveillance, Epidemiology, and End Results (SEER) Program database was used to identify patients diagnosed with GBC and undergoing surgery between 2004 and 2015. The patients were divided into the S, AC, and ACR groups according to their treatment. Categorical variables were compared by Pearson's chi-square test, and a 1:1:1 propensity score matching analysis (PSM) was performed. Overall survival was assessed by Kaplan-Meier curves with log-rank tests. Subgroup analyses were conducted. Result: A total of 5451 patients were identified in the SEER database. After PSM, the two-year survival among patients who received S, AC, and ACR was 36%, 39%, and 45%, respectively. ACR was associated with improved two-year survival ( p < 0.001), while the survival rates were similar in the AC and S groups ( p = 0.127) but better in the ACR group than in the AC group ( p = 0.012). Subgroup analyses indicated that while the two-year survival rates did not differ significantly in stage II GBC patients between the groups (all p > 0.05), ACR was associated with significantly improved two-year survival in stage Ⅲa ( p = 0.008), Ⅲb ( p < 0.001), and Ⅳb ( p < 0.001) GBC patients. Conclusion: The combination of surgery and ACR as the treatment modality provided greater survival benefits for GBC patients, particularly for those with advanced tumor staging.